External Mass Compressing the Left Atrium on Transthoracic Echocardiography - Im, Eun-Joo; Oh, Su-Sung; Kang, Kyung-Mi; Kim, Ji-Hoon; Moon, Keon-Woong; Yoo, Ki-Dong; Kim, Chul-Min (Korean circulation journal, 2010)
KCI Citation Count: 0